Providing Guidance and Counseling Services in Time of Covid-19 Pandemic: Lived Experiences of Guidance Designates - Salvador, Normie; Singson, Deborah Natalia; Madrigal, Dennis; Bual, Joel (Technium Social Sciences Journal, 2024)
The pandemic era has directed a new facade of education from traditional to a more conducive system of virtual and modular schemes. The Guidance Designates are equally tasked to play a crucial part in this abrupt transition as the teachers. They, too, are directed to maintain relationships on top of the delivery of guidance and counseling services at the height of the COVID-19 pandemic to meet the needs of students and families and let the education roll. This descriptive phenomenological study was conducted to explore the lived experiences of public junior high school guidance designates in the delivery of guidance and counseling services during the pandemic. The participants of this study were five guidance designates in public junior high schools identified using purposive sampling who took part in the unstructured in-depth interview. The study revealed that guidance designates faced issues, struggles, and sentiments in the delivery of guidance services during the time of pandemic. They utilized various alternatives for the delivery of appropriate services to clients despite unreachable ones. Despite their feelings of boredom and loneliness, they found meaning in their chosen profession by becoming grateful for the designation, and their commitment to serving the clients ignited the passion to go on despite the odds. Their enjoyment with colleagues acts as their strong social support during the crucial times of the pandemic. Thus, these experiences honed them to be shade shifters that remained resilient and flexible in the delivery of guidance and counseling services in the pandemic era.